Advances in the steady-state hybrid regime in DIII-D—a fully non-inductive, ELM-suppressed scenario for ITER. (31st August 2017) - Petty, C.C.; Nazikian, R.; Park, J.M.; Turco, F.; Chen, Xi; Cui, L.; Evans, T.E.; Ferraro, N.M.; Ferron, J.R.; Garofalo, A.M.; Grierson, B.A.; Holcomb, C.T.; et al.
Abstract: The hybrid regime with beta, collisionality, safety factor and plasma shape relevant to the ITER steady-state mission has been successfully integrated with ELM suppression by applying an odd parity n   =  3 resonant magnetic perturbation (RMP). Fully non-inductive hybrids in the DIII-D tokamak with high beta ( ⟨ β ⟩   ⩽  2.8%) and high confinement (H98y2   ⩽  1.4) in the ITER similar shape have achieved zero surface loop voltage for up to two current relaxation times using efficient central current drive from ECCD and NBCD. The n   =  3 RMP causes surprisingly little increase in thermal transport during ELM suppression. Poloidal magnetic flux pumping in hybrid plasmas maintains q above 1 without loss of current drive efficiency, except that experiments show that extremely peaked ECCD profiles can create sawteeth. During ECCD, Alfvén eigenmode (AE) activity is replaced by a more benign fishbone-like mode, reducing anomalous beam ion diffusion by a factor of 2. While the electron and ion thermal diffusivities substantially increase with higher ECCD power, the loss of confinement can be offset by the decreased fast ion transport resulting from AE suppression. Extrapolations from DIII-D along a dimensionless parameter scaling path as well as those using self-consistent theory-based modeling show that these ELM-suppressed, fully non-inductive hybrids can achieve the Q fus   =  5 ITER steady-state mission.